Osteochondritis dissecans of the capitellum in adolescents - van Bergen, Christiaan JA (World J Orthop, 2016)
Osteochondritis dissecans (OCD) is a disorder of articular cartilage and subchondral bone. In the elbow, an OCD is localized most commonly at the humeral capitellum. Teenagers engaged in sports that involve repetitive stress on the elbow are at risk. A high index of suspicion is warranted to prevent delay in the diagnosis. Plain radiographs may disclose the lesion but computed tomography and magnetic resonance imaging are more accurate in the detection of OCD. To determine the best treatment option it is important to differentiate between stable and unstable OCD lesions. Stable lesions can be initially treated nonoperatively with elbow rest or activity modification and physical therapy. Unstable lesions and stable lesions not responding to conservative therapy require a surgical approach. Arthroscopic debridement and microfracturing has become the standard initial procedure for treatment of capitellar OCD. Numerous other surgical options have been reported, including internal fixation of large fragments and osteochondral autograft transfer. The aim of this article is to provide a current concepts review of the etiology, clinical presentation, diagnosis, treatment, and outcomes of elbow OCD.